Atrial natriuretic peptide inhibits mineralocorticoid receptor function in rat colonic surface cells. - Schulman, G (1996)
Atrial natriuretic peptide (ANP) inhibits and aldosterone (ALDO) stimulates Na conductive transport. Therefore, the effects of ANP and its second messenger cGMP on mineralocorticoid receptor (MR) function in rat colon surface and crypt cells were examined. 100 nM 8-Br-cGMP decreased surface [3H]ALDO binding by 42 +/- 4% but increased crypt [3HvALDO binding by 52+/-16%. ANP decreased surface [3H]ALDO binding by approximately 50% after a 2.5-h lag period but had no effect on crypt ALDO binding. ANP and cGMP rapidly (< 15 min) inhibited surface cell ALDO-induced MR nuclear translocation but did not affect crypt MR nuclear translocation. Inhibition of cGMP-dependent protein kinase with KT5823 blocked the inhibitory effects of ANP and 8-Br-cGMP on surface cell ALDO binding and MR nuclear translocation. In crypt, KT5823 increased baseline [3H]ALDO binding but did not inhibit the stimulatory effect of exogenous cGMP. DEAE-cellulose chromatography and gel mobility shift assay showed that ANP did not inhibit surface MR activation. ANP inhibited ALDO stimulated short circuit current in distal colon. These data demonstrate cell-specific regulation of MR function. In surface cells, ANP rapidly inhibits MR nuclear translocation and ALDO-induced short circuit current. ANP inhibition of MR function may be an additional mechanism of ANP antagonism of Na reabsorption.